Adsorption of Lead, Arsenic and Mercury from Industrial Effluent Using Low-Cost Agro-Waste - Tijjani, B.; Yaumi, A. L.; Mohammed, H. D.; Umar, H.; Yakubu, E.; Highina, B. K. (International Journal of Environment, 2024)
Heavy metal contamination in industrial effluents poses significant environmental and health risks, necessitating the development of effective, low-cost adsorbents. This study explored the potential of Millet Husk and Millet Straw, agricultural waste materials, for the removal of Lead (Pb), Arsenic (As), and Mercury (Hg) from industrial effluents. Millet Husk and Millet Straw activated carbon (MHS) was prepared through sodium hydroxide (NaOH) activation and characterized using Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), and Energy Dispersive X-ray Spectroscopy (EDX). Batch adsorption experiments were conducted to assess the performance of MHS in removing heavy metals from effluent samples, with removal efficiency analyzed using Atomic Absorption Spectrometry (AAS). Characterization results revealed that MHS exhibited enhanced surface morphology, high porosity, and functional groups that facilitated heavy metal adsorption. The optimal removal efficiencies were 58.67% for Pb, 69.83% for As, and 100% for Hg. Factors such as adsorbent dosage, contact time, and pH significantly influenced adsorption rates, with maximum adsorption observed at a dosage of 0.1 g. The study concluded that MHS is a promising adsorbent for heavy metal removal from wastewater, with its adsorption capacity dependent on initial metal concentrations and pH levels. Further research is recommended to explore the scalability of MHS in real-world applications, investigate modifications to enhance its adsorption capabilities, and study its regeneration and reuse potential for long-term viability as an eco-friendly adsorbent.